Latent Class Analysis of Dental Treatment: Observed in IIUM Dental Specialist Clinic, Kuantan, Pahang - Kharuddin, Azrul Fazwan; Ismail, Khadilla; Ghazali@Suhaimi, Siti Sarah; Abu Bakar, Noraini; Mokhtar, Khairani Idah (IIUM Medical Journal Malaysia, 2018)
Research into dental treatment via statistical perspective was unraveled through a relation between theoretical and experimental probability. This assessment of association was examined using statistical test over Confirmatory Factor Analysis (CFA) and Latent Class Analysis (LCA). Theoretical results of the prevailing difference between the direct and indirect upshot was verified through a technique known as integrated model by using Mplus® software package. The results expressively show that the dental treatment from the indirect effect has better performance than the direct effect. Besides that, there is a dramatic improvement of dental treatment from different type of malocclusion analysis. Three classes of different type of malocclusion analysis play an important role as mediator for demographic variable and type of dental treatment.